PANDANGAN GABRIEL MARCEL TENTANG MANUSIA DALAM KONTEKS PERISTIWA BENCANA ALAM - Septiana Dwiputri Maharani (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2012)
In this time, there are a lot of accidents, like flood, landslide, fire, dryness, storm, tsunami, earthquake, and mount eruption. A lot of victims in these disasters. The victim have never represented an object choice, even victim have never chosen. Social reality describing to live together that demand a good social relationship and interaction of intersubjectivity. The Gabriel Marcel’s concept is the most relevant concept. The problems are what is the nature of “I” according to Marcel? How about the concept of relation of intersubjectivity? What is the concept of Love and Hope? What relevancy the Gabriel Marcel’s concept with human and emphaty with the victim of disaster? The Result of research are: According to Marcel’s view of existence of human being cannot be objectivied. The existence is my real experience as a subject in the world. In other word, existence represents the complexity of all factors that signs my live. Because of Marcel’concept gave appreciation for relation, he sure that man is the dynamic creature, always be achieve the level of to be. This level require to be confessed because to become to be myself, somebody will depend on its relationship. Intersubjective relationship according to Marcel marked with attendance. The mystery of human being is on this relationship. Attendance represents the meeting I – Thou, not only be comprehended simply as a meeting someone in the space. Attendance realized with the love, and faithfulness. These unsure are the important elements in understand and feel disaster victim, not as an object felt pity. Expectation will penetrate the certainty, which can make the calm human being and not afraid to death, also for the disaster. Expectation will appear the belief. Despair becaused of losing the expectation, belief, and love. These elements will realize the awareness to the eternity love, inclusive of God. Love represents the philosophic key on Marcel’concept which find the balance solution. Love gives the meaning of intersubjective relationship. With Love, the object will never died. Love gives the eternity meaning, to remove the hate each other, like expectation when removing the fear, despair. The contrary, expectation gives someone the confidence, certainty to uncertainty. Love and expectation confirm the self- faithfulness to the others inclusive of God.